2013
DOI: 10.1111/jth.12401
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor remodeling during exocytosis from vascular endothelial cells

Abstract: Summary. Background: In vascular endothelial cells, high molecular weight multimers of von Willebrand factor (VWF) are folded into tubular structures for storage in Weibel-Palade bodies. On stimulation, VWF is secreted and forms strings to induce primary hemostasis. The structural changes composing the transition of stored tubular VWF into secreted unfurled VWF strings are still unresolved even though they are vital for normal hemostasis. The secretory pod is a novel structure that we previously described in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
0
35
2
Order By: Relevance
“…Both FVIII and ultra-large multimers of VWF (ULVWF) are packaged in the WeibelPalade bodies of select types of primary endothelial cells [5,6]. Upon secretion of the granules, strings of ULVWF anchored on the cell surface are cleaved by the metalloprotease ADAMTS13 into smaller FVIII/ VWF multimers [6,7], while pH-induced dissociation of VWF propeptide allows both FVIII to bind and FVIII/VWF multimers to adopt a globular conformation [8]. Given the different sizes of VWF multimers (up to 20 000 kDa) vs. FVIII (approximately 300 kDa) and the different stoichiometric proportion (50-100 VWF molecules per 1 FVIII molecule) [9], FVIII represents only 1-2% of the total protein composition within the natural FVIII/VWF complex.…”
Section: Referencesmentioning
confidence: 99%
“…Both FVIII and ultra-large multimers of VWF (ULVWF) are packaged in the WeibelPalade bodies of select types of primary endothelial cells [5,6]. Upon secretion of the granules, strings of ULVWF anchored on the cell surface are cleaved by the metalloprotease ADAMTS13 into smaller FVIII/ VWF multimers [6,7], while pH-induced dissociation of VWF propeptide allows both FVIII to bind and FVIII/VWF multimers to adopt a globular conformation [8]. Given the different sizes of VWF multimers (up to 20 000 kDa) vs. FVIII (approximately 300 kDa) and the different stoichiometric proportion (50-100 VWF molecules per 1 FVIII molecule) [9], FVIII represents only 1-2% of the total protein composition within the natural FVIII/VWF complex.…”
Section: Referencesmentioning
confidence: 99%
“…By LM, we identified a novel structure involved in VWF exocytosis, the secretory pod. This structure is only present in stimulated endothelial cells and appears as a large VWF positive spherical-shaped structure that associates with WPBs and VWF strings (Mourik et al, 2013;Valentijn et al, 2010). Transmission electron microscopy (TEM) revealed that stimulated endothelial cells contained large membrane-enclosed organelles of similar dimensions.…”
Section: Introductionmentioning
confidence: 96%
“…The membrane-enclosed organelles contained lacy material and were often in close proximity with WPBs. To show that the structures observed by TEM contained VWF and represented, the VWF-positive secretory pods seen by LM, CLEM was performed (Mourik et al, 2013;Valentijn et al, 2010). We combined confocal laser scanning microscopy with conventional TEM and electron tomography to reveal the structures in three dimensions using serial sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated a marked unbalance between the platelet binding protein von Willebrand factor (VWF) and its cleaving protease: A disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13), in plasma of brain dead organ donors (1). This unbalance is indicative of an increased activity of the endothelial cells after brain death (1,2). Continuous extensive VWF release by activated endothelial cells may lead to the consumption of ADAMTS13 until the levels of the molecule are insufficient to process VWF (3).…”
Section: Introductionmentioning
confidence: 99%